Efforts of the Narcotics Detective Unit in Combating Drug Abuse in the Jurisdiction of Temanggung Police Resort - Dalimunthe, Thohiro Muhammad Said (Advances in Police Science Research Journal, 2024)
The author addresses the issue of increasing drug abuse cases in the jurisdiction of the Temanggung Police Resort, which is caused by the lack of optimal efforts by the narcotics detective unit. From the research conducted by the author, there are three efforts in combating drug abuse: preventive, repressive, and curative (rehabilitation). The issues in this final project are (1) how is the management of drug abuse handling by the narcotics detective unit in the Temanggung Police Resort, and (2) how effective is the handling of drug abuse by the narcotics detective unit in the Temanggung Police Resort. This final project research uses a qualitative approach. For the analysis tool, the author uses the POAC Management Theory, Legal Effectiveness Theory, and SWOT Analysis Theory, as well as the concepts of efforts, combating, and drug abuse. The research found that the efforts of the narcotics detective unit in combating drug abuse are still not carried out optimally, as they only handle drug abuse cases with repressive/law enforcement measures. This is due to three factors: the lack of quality and quantity of personnel, minimal facilities and infrastructure, and insufficient budget that supports the high disclosure of drug cases. In response to these issues, the author proposes several solutions, such as cooperation with community organizations and the National Narcotics Agency of Temanggung District, utilization of the Integrated Assessment Team for the Rehabilitation of Narcotics Abuse Suspects, providing opportunities to improve knowledge through special drug training for members, optimization of the detective unit’s activities in the Temanggung Police Resort, optimization of facilities and infrastructure, and coordination and cooperation with the National Narcotics Agency of Temanggung District and the community. The author also suggests to the leadership to (1) increase the number of personnel in the narcotics detective unit of the Temanggung Police Resort, (2) provide facilities and infrastructure that support the handling of drug abuse, and (3) allocate a special budget for preventive and curative activities carried out by the narcotics detective unit of the Temanggung Police Resort.